1998
DOI: 10.1007/s005920050099
|View full text |Cite
|
Sign up to set email alerts
|

With regard to glycohemoglobin measurement: are we sure that high-performance liquid chromatography currently works in the clinical routine?

Abstract: The clinical usefulness of glycated hemoglobin (HbA1C) depends crucially on the accuracy and precision of its assay. When we compared an immunological bench-top analyzer (DCA 2000, Bayer Diagnostici, Milan) to the high-performance liquid chromatography (HPLC) reference method used in a routine hospital laboratory (Diamat and Fast Diamat, Bio-Rad Lab., Milan) by assaying multiple control sera, we found so many sources of systematic analytical errors in the routine use of HPLC as to compromise between-assay prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The performance of these devices in this study was consistent with that found by other researchers (DCA 2000 [27][28][29][30][31][32][33][34][35][36][37] ; DCA Vantage [38][39][40]. During this study, the analytical quality of the established POCT devices and a number of new devices was assessed along with stakeholder satisfaction relating to the POCT service.…”
Section: Discussionsupporting
confidence: 87%
“…The performance of these devices in this study was consistent with that found by other researchers (DCA 2000 [27][28][29][30][31][32][33][34][35][36][37] ; DCA Vantage [38][39][40]. During this study, the analytical quality of the established POCT devices and a number of new devices was assessed along with stakeholder satisfaction relating to the POCT service.…”
Section: Discussionsupporting
confidence: 87%